(untitled) (Fiep Bulletin - online, 2016)
Introduction: Parkinson’s disease (PD) is a neurodegenerative disorder of the central nervous system characterized by resting tremor, muscle rigidity, bradykinesia and postural instability. Objective: The aim of this paper is to assess and characterize PD sufferers according to the stage of the disease and quality of life. Materials and methods: The patients were approached in a Therapeutic Group which happened in a specialized institution. The sample was made of 20 patients, of both genders, with an average age of 71,75±3,04 years old and an average time of the diagnosis of the disease of 5,55±2,96 years old. To assess the stage of the disease it was used Hoehn e Yahr Staging Scale of Incapacity (HY), and to assess the patients’ quality of life Parkinson’s Disease Questionnaire (PDQ-39) was conducted. Results: The analysis of HY revealed an average score of 3,0, characterizing a mild bilateral impairment. In PDQ-39 the total average score was 38,20 since the Mobility, ADL, Emotional Well-being and Cognition were the most stricken by PD. Conclusion: It was verified that the researched patients did not fill the most advanced stages of the disease and present the quality of life and mobility impaired by PD.